Implementation of the Village/Kelurahan Merger Process in Areas Affected By Lapindo Lumpur - prayoga, Akbar; Sukristyanto, Agus; Kusbandrijo, Bambang (Jurnal Ad'ministrare: Jurnal Pemikirian Ilmiah dan Pendidikan Administrasi Perkantoran, 2024)
The Sidoarjo Hot Mud Disaster which inundated several villages in the Porong, Jabon and Tanggulangin Districts caused various problems including social, political, economic problems as well as the paralysis of government services including services in the fields of education, health and regional administration carried out by the Village/District Governments affected by the mud. The areas affected by the mudflow are in accordance with the Map of Areas Affected by Mud Disasters in the attachment to Presidential Regulation No. 21 of 2017 concerning the Sidoarjo Mud Management Agency covering 2 villages in Jabon District, namely Besuki Village and Pejarakan Village, 1 Village, namely Renokenongo Village and 3 Villages, namely Mindi Village, Jatirejo Village and Siring Village in Porong District, 2 Villages in Tanggulangin District, namely Ketapang Village and Kedungbendo Village. In this research, a qualitative descriptive approach was used using interview, observation and documentation data collection techniques. This research uses program implementation theory by David C. Korten to determine the implementation of the Village/Subdistrict merger program in affected areas through 3 program implementation indicators, namely, Program, Implementing Organization and Group Targets. The results of the research state that the Sidoarjo Regency Government has implemented programs as an implementation of Regent Regulation Numbers 1 and 4 concerning the Merger of Subdistricts and Villages in Sidoarjo Mudflow Affected Areas. In interviews and observations conducted by the author, obstacles were also found in the implementation of the program, namely, the regulations regarding the merger of villages and sub-districts affected by mud still do not fully accommodate the problems that occur when merging villages and sub-districts affected by mud in Sidoarjo Regency